theorem all2all2 (A: set) (l1 l2: nat) {x: nat}: $ l1, l2 e. all2 (S\ x, A) -> all A l2 $;
Step | Hyp | Ref | Expression |
---|---|---|---|
1 |
all A l2 <-> A. n A. a1 (nth n l2 = suc a1 -> a1 e. A) |
||
2 |
l1, l2 e. all2 (S\ x, A) <-> len l1 = len l2 /\ A. n A. a2 (nth n l1 = suc a2 -> A. a1 (nth n l2 = suc a1 -> a2, a1 e. S\ x, A)) |
||
3 |
x = a2 -> (a1 e. A <-> a1 e. A) |
||
4 |
a2, a1 e. S\ x, A <-> a1 e. A |
||
5 |
A. a1 (nth n l2 = suc a1 -> a2, a1 e. S\ x, A) <-> A. a1 (nth n l2 = suc a1 -> a1 e. A) |
||
6 |
A. a2 (nth n l1 = suc a2 -> A. a1 (nth n l2 = suc a1 -> a2, a1 e. S\ x, A)) <-> A. a2 (nth n l1 = suc a2 -> A. a1 (nth n l2 = suc a1 -> a1 e. A)) |
||
7 |
A. a2 (nth n l1 = suc a2 -> A. a1 (nth n l2 = suc a1 -> a1 e. A)) <-> A. a1 (nth n l2 = suc a1 -> A. a2 (nth n l1 = suc a2 -> a1 e. A)) |
||
8 |
E. a2 nth n l1 = suc a2 -> a1 e. A <-> A. a2 (nth n l1 = suc a2 -> a1 e. A) |
||
9 |
E. a2 nth n l1 = suc a2 -> (E. a2 nth n l1 = suc a2 -> a1 e. A) -> a1 e. A |
||
10 |
nth n l1 != 0 <-> E. a2 nth n l1 = suc a2 |
||
11 |
nth n l1 != 0 <-> n < len l1 |
||
12 |
len l1 = len l2 /\ nth n l2 = suc a1 -> len l1 = len l2 |
||
13 |
len l1 = len l2 /\ nth n l2 = suc a1 -> (n < len l1 <-> n < len l2) |
||
14 |
nth n l2 != 0 <-> n < len l2 |
||
15 |
nth n l2 = suc a1 -> nth n l2 != 0 |
||
16 |
nth n l2 = suc a1 -> n < len l2 |
||
17 |
len l1 = len l2 /\ nth n l2 = suc a1 -> n < len l2 |
||
18 |
len l1 = len l2 /\ nth n l2 = suc a1 -> n < len l1 |
||
19 |
len l1 = len l2 /\ nth n l2 = suc a1 -> nth n l1 != 0 |
||
20 |
len l1 = len l2 /\ nth n l2 = suc a1 -> E. a2 nth n l1 = suc a2 |
||
21 |
len l1 = len l2 /\ nth n l2 = suc a1 -> (E. a2 nth n l1 = suc a2 -> a1 e. A) -> a1 e. A |
||
22 |
len l1 = len l2 /\ nth n l2 = suc a1 -> A. a2 (nth n l1 = suc a2 -> a1 e. A) -> a1 e. A |
||
23 |
len l1 = len l2 -> nth n l2 = suc a1 -> A. a2 (nth n l1 = suc a2 -> a1 e. A) -> a1 e. A |
||
24 |
len l1 = len l2 -> (nth n l2 = suc a1 -> A. a2 (nth n l1 = suc a2 -> a1 e. A)) -> nth n l2 = suc a1 -> a1 e. A |
||
25 |
len l1 = len l2 -> A. a1 (nth n l2 = suc a1 -> A. a2 (nth n l1 = suc a2 -> a1 e. A)) -> A. a1 (nth n l2 = suc a1 -> a1 e. A) |
||
26 |
len l1 = len l2 -> A. a2 (nth n l1 = suc a2 -> A. a1 (nth n l2 = suc a1 -> a1 e. A)) -> A. a1 (nth n l2 = suc a1 -> a1 e. A) |
||
27 |
len l1 = len l2 -> A. a2 (nth n l1 = suc a2 -> A. a1 (nth n l2 = suc a1 -> a2, a1 e. S\ x, A)) -> A. a1 (nth n l2 = suc a1 -> a1 e. A) |
||
28 |
len l1 = len l2 -> A. n A. a2 (nth n l1 = suc a2 -> A. a1 (nth n l2 = suc a1 -> a2, a1 e. S\ x, A)) -> A. n A. a1 (nth n l2 = suc a1 -> a1 e. A) |
||
29 |
len l1 = len l2 /\ A. n A. a2 (nth n l1 = suc a2 -> A. a1 (nth n l2 = suc a1 -> a2, a1 e. S\ x, A)) -> A. n A. a1 (nth n l2 = suc a1 -> a1 e. A) |
||
30 |
l1, l2 e. all2 (S\ x, A) -> A. n A. a1 (nth n l2 = suc a1 -> a1 e. A) |
||
31 |
l1, l2 e. all2 (S\ x, A) -> all A l2 |